Legal Perspective On Notary As General Officer Of Authentic Assets And Its Legal Expression - Mustholih Baidlowi (Sultan Agung Notary Law Review, 2020)
Notary is a public official who has the authority to make authentic deeds and has other powers as referred to in Act No. 2 of 2014 concerning Amendments to Act No. 30 of 2004 concerning the Position of a Notary. Notaries as public officials who make authentic deeds have an important role in ensuring legal certainty for the people who use their services. The purpose of this research is to find out and understand the legal position of authentic deeds that are legally owned. The method used in this research is sociological juridical method, the specification in this research is descriptive analytical, the data used are primary data and secondary data, using data collection by interview and literature study. The results of this study indicate thatauthentic deeds have 2 (two) main functions, namely, as a formal function (formality causa) and function as evidence (probationis causa). The formal function (formality causa) means that to make an act declared complete and perfect (not to be valid) a legal act must be made in the form of an authentic deed. Functioning as evidence (probationis causa) it can be interpreted that the authentic deed is deliberately made as proof at a later date. A deed can be categorized as an authentic deed if the deed is drawn up in accordance with the procedures that have been determined based on the provisions of Article 38 of the Law on the Position of Notary Public. A Notary deed can be said to meet the requirements as an authentic deed if the Notary deed is in accordance with the procedures and procedures that have been determined based on the provisions of Article 39 of the Law on the Position of Notary up to Article 53 of the Law on the Position of Notary Public.